2022
DOI: 10.1002/jgt.22864
|View full text |Cite
|
Sign up to set email alerts
|

On the hamiltonicity of a planar graph and its vertex‐deleted subgraphs

Abstract: Tutte proved that every planar 4-connected graph is hamiltonian. Thomassen showed that the same conclusion holds for the superclass of planar graphs with minimum degree at least 4 in which all vertex-deleted subgraphs are hamiltonian. We here prove that if in a planar n-vertex graph with minimum degree at least 4 at least n − 5 vertex-deleted subgraphs are hamiltonian, then the graph contains two hamiltonian cycles, but that for every c < 1 there exists a nonhamiltonian polyhedral n-vertex graph with minimum d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…We briefly comment on the observation used in Figure 2 to obtain a triangulation-for results on the interaction between n-and (n − 1)-cycles in n-vertex triangulations we refer to [15]. For all graphs proving the statement of Theorem 3, we chose the graph J to be, for every replacement, the octahedron minus the edges of a triangle (as before, the identified vertices shall be the three 2-valent vertices of the octahedron minus the edges of a triangle).…”
Section: Theoretical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We briefly comment on the observation used in Figure 2 to obtain a triangulation-for results on the interaction between n-and (n − 1)-cycles in n-vertex triangulations we refer to [15]. For all graphs proving the statement of Theorem 3, we chose the graph J to be, for every replacement, the octahedron minus the edges of a triangle (as before, the identified vertices shall be the three 2-valent vertices of the octahedron minus the edges of a triangle).…”
Section: Theoretical Resultsmentioning
confidence: 99%
“…It was recently shown that in the statement of ( †), the second "n" can be replaced by n − 5, see [15]. It is natural to wonder how much more this threshold can be lowered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation